Pengaruh Sense of Humor dan Self Compassion Terhadap Resiliensi Akademik pada Mahasiswa Universitas Syiah Kuala Banda Aceh - Yana Humaira; Asih Menanti; Salamiah Sari Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims (1) to determine the effect of sense of humor on academic resilience; (2) To determine the effect of compassion on academic resilience;(3) To determine the effect of sense of humor and compassion on academic resilience. This research is quantitative research. The population in this study were Syiah Kuala University students with a sample of 158 students. Sampling using simple random sampling technique. The measuring instruments used in this study were the sense of humor scale (SHQ), the self-compassion scale (SCS) and the academic endurance scale (ARS-30). Data analysis used multiple regression analysis. The results showed that (1) there was a significant positive effect between sense of humor and academic resilience as seen from (Rxly) = 0.413 with P = 0.000 < 0.050 meaning that there was a positive influence between sense of humor and academic resilience; (2) there is a significant positive effect between self-love and academic resilience as seen from (Rxly) = 0.277 with P = 0.000 < 0.050 meaning that there is a positive influence between self-love and academic resilience; (3) there is a significant positive effect between sense of humor, self-love and academic resilience as seen from (Rxly) = 0.460 with P = 0.000 < 0.050 meaning that there is a positive influence between sense of humor, self-love and academic resilience. The percentage of contribution given by the simultaneous influence of sense of humor and self- compassion on academic resilience is 21.1%. The remaining 79.9% is influenced by other variables not examined in this study.